EKSISTENSI TARI JEPIN LANGKAH SERONG DI KOTA PONTIANAK KALIMANTAN BARAT - Hermansyah Hermansyah; Ismunandar Ismunandar; Regaria Tindarika (Universitas Tanjungpura, 2021)
Abstract This study aims to describe the Exixtence of the Jepin Langkah Serong dance in the city of Pontianak. The problem of this research is related to the ekxistence of the Jepin Langkah Serong dance in the city of Pontianak and the factors that influence the existence of the dance. The research uses descriptive methods in the form qualitative and historical approaches. The sources of data in this study are Mr. Juhermi Tahir, Mrs. Kusmindari Triwati and Mr. Yuni Syahroni who know the Jepin Langkah Serong Dance. Data collection techniques in the fprm of observation, interviews and documentation studies. The technique of testing the validity of the data used is source triangulation. The result of this research is the Jepin Langkah Serong Dance is lifted and preserved by the Andari Studio and the Gita Natia Studio. Factors supporting the existence of the dance are art organizations, government agencies, community support and the FKIP UNTAN arts campus. The inhibiting factors for the existence of this dance are the impact of blobalization, the economic crisis and the COVID-19 Pandemi. Efforts to preserve it are to foster public interest, government appreciation and social media. Keywords: Existence, Jepin Langkah Serong Dance